Activating catalytic behavior of binary transition metal sulfide-shelled carbon nanotubes by iridium incorporation toward efficient overall water splitting. (March 2023) - Zhu, Xinfeng; Nguyen, Dinh Chuong; Prabhakaran, Sampath; Kim, Do Hwan; Kim, Nam Hoon; Lee, Joong Hee
Abstract: To meet the future demand for green energy, the development of catalysts for water splitting has become an essential task for scientists worldwide. In this context, a novel catalyst that relies on Ir-doped CoNi2 S4 nanosheets assembled on carbon nanotubes, supported on three-dimensional carbon framework has been developed. The outstanding advantages of core-shell heterostructure and heteroatom doping are that they induce high abundance of exposed active sites and excellent ability for mass/charge transport of the catalyst. Thus, the catalyst provides excellent activity for hydrogen evolution reaction, which surpasses that of the noble-metal-free electrocatalysts reported in the literature. The catalyst also shows superior catalytic behavior for oxygen evolution reaction, which is even better than that of the commercial RuO2 catalyst. Impressively, the electrolyzer using the proposed catalyst requires small cell voltages of only 1.60 V and 1.94 V at response current density of 10 mA/cm 2 and 50 mA/cm 2, respectively. More importantly, this electrolyzer manifests much better stability and durability than those of the electrolyzer using commercial Pt/C and RuO2 catalysts. Graphical abstract: Image 1 Highlights: Ir-doped CoNi2 S4 nanosheets assembled on carbon nanotubes is grown on three-dimensional carbon framework. The proposed material acts as a bifunctional electrocatalyst with good catalytic performance and superior robustness for overall water splitting. The core-shell heterostructure and heteroatom doping are of great significance to improve the catalytic efficiency.